Research highlights: nanopore protein detection and analysis1. Issue 17 (7th September 2015) - Acharya, Shiv; Edwards, Shayson; Schmidt, Jacob
<x xml:space="preserve">Abstract</x> Nanopore detection of specific protein species using carrier DNA – Quantitative protein concentration determination using aptamers – Protein folding studied with unfoldase-coupled nanopores.